Platform for Alternative Feed Ingredients Evaluation (PAFIE) - Black soldier fly larvae (BSFL) in Kenya - Ouma, Emily A.; Lukuyu, Ben A.; Githinji, Julius (International Livestock Research Institute, 2026)
Commercial livestock feeds primarily rely on plant-based protein sources such as corn and soybean. However, these ingredients are highly susceptible to price instability and supply disruptions due to their dependence on rainfed agriculture and generally low productivity. This challenge is especially pronounced for small-scale farmers, who often cannot afford commercial feeds, resulting in limited access and low livestock productivity.